Analysis Of The Concept Of Religious Deradicalization As The Modernization Of Islam In Hamka Haq's Thinking - Sujarwo; Putri, Widia; Victorius, Dhimas; Maharani, Fuan (Sekolah Tinggi Agama Islam (STAI) Bumi Silampari, 2026)
The purpose of this research is to provide understanding tolerance to Muslims related to radical or fundamentalist ideologies so that with this deradicalization can reduce ideologies that can be dangerous for other religious adherents or fellow Muslims themselves. The data analysis technique used is This research uses a descriptive qualitative research method with a type of library research. which is presented in descriptive form which is ultimately expected to be able to provide a comprehensive view of the role of modernization as one of the efforts to overcome radical movements. This research emphasizes the intended data sources are of course related to strengthening religious moderation from the perspective of Islamic religious education to understand the importance of the position of religious deradicalization in strengthening religious moderation literacy. The idea of ??this research is related to religious modernization, namely that Islam must be able to bring peace, justice, and universal benefits and also Islam is not only seen from a normative-theological perspective, but also as a socio-political ethic that guides people in national and state life so that it is hoped that it can make its ideas about religious deradicalization as one of the references in formulating religious education policies so as to offer a holistic and transformative character education model.